Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1177/152660289900600407
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Hemorrhage after Carotid Stenting

Abstract: Purpose: To report an important complication related to carotid stenting. Methods and Results: A 71-year-old man with symptomatic subtotal occlusion of the left internal carotid artery had a 30-mm lesion treated percutaneously with implantation of 2 stents. Although the procedure was completed satisfactorily, left intraventricular hemorrhage occurred 4 hours later, possibly related to hyperperfusion injury. The patient expired 30 days after the stent procedure. Preoperative single-photon emission computed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Five cases of hyperperfusion syndrome with resultant hemorrhage following extracranial carotid intervention have been reported [2][3][4][5]. These reports demonstrate the similarity of this syndrome to the surgical counterpart in terms of clinical presentation and outcome.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Five cases of hyperperfusion syndrome with resultant hemorrhage following extracranial carotid intervention have been reported [2][3][4][5]. These reports demonstrate the similarity of this syndrome to the surgical counterpart in terms of clinical presentation and outcome.…”
Section: Discussionmentioning
confidence: 85%
“…A similar syndrome of hyperperfusion that is complicated by intracranial bleeding following carotid intervention has recently been described [2][3][4][5]. Although it appears to be rare, occurring in 0.3% of our total experience, the devastating outcome of this complication obligates the awareness of the clinical manifestation and the recognition of the predisposed patients in order to initiate timely and appropriate management.…”
Section: Introductionmentioning
confidence: 92%
“…1 Hemorrhage associated with classic hyperperfusion syndrome usually develops within a few days after procedures, [2][3][4][5] and hyperacute hemorrhage can occur within several hours of CAS. 1,[6][7][8][9][10][11][12][13][14][15][16][17] Here, we describe putaminal hemorrhage with angiographic extravasation immediately after CAS. The etiology of hyperacute hemorrhage would differ from that of classic hyperperfusion syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…McCabe et al (1999) reported the first fatal case of ICH after CAS, a man with severe stenosis who developed ICH within hours of CAS without any prodromes. Mori et al (1999) reported a similar case in which ICH affected the basal zones with ventricular and subarachnoid extension. Both cases had signs of microangiopathy, which is associated with increased risk of ICH (Chamorro et al, 2000;McCabe et al, 1999).…”
Section: Angioplasty Various Techniques and Challenges In Treatment mentioning
confidence: 87%